A Factorial Analysis of Information Ratio and Its Causal Effect on Yearly Return of Net Asset Value – A Study of Indian Equity Diversified Mutual Fund Schemes - Chakraborty, Suman; Kumar, Satish; Shawn Lobo, Lumen (International Journal of Engineering and Technology, 2018)
Evaluation of performance of mutual fund schemes has gained a wide range of attention from both investors and academicians. The study aims at assessing the returns from equity mutual fund schemes in India by applying risk adjusted performance evaluation techniques. The study is based on secondary data collected for ten years for selected open ended equity diversified mutual funds. A comparative assessment of performance of public sector sponsored equity funds and non-government sponsored Â sector funds bring forth with an interesting inference. The present study also constitutes a modest attempt to assess the information ratio and its causal effect on the average yearly return of Net Asset Value (NAV). Based on the previous research findings, this paper puts an honest effort to identify twelve independent variables which affects significantly the performance of NAV. The evaluation relies on the Sharpe, Trenor and Jensenâ€™s technique, which have been applied in conjunction with parametric and non-parametric statistical tools using. The result shows significant relationship exists between the NAV return and fundâ€™s risk, information ratio, macro-economic variables such as inflation, interest rates, market index performance, foreign flow of funds and foreign exchange on the basis of regression analysis.Â